Capturing constraint evolution: a technique to preserve and handle design knowledge. (16th November 2011) - Ding, Lian; Matthews, Jason; Mullineux, Glen
Product development can be considered as the evolutionary and iterative process of recognition, formulation and satisfaction of constraints. These become the rationale driving the design to the final specifications, with the evolution of constraints reflecting the design process, and decisions made by designers. This paper proposes an approach that allows the designer to annotate product models with constraints, which can be used to optimise the design by monitoring and adapting the constraints. It is also proposed that the evolving constraints can then be used to retrace the engineering decision-making processes, thus aiding new designers to assimilate and digest the design.